Synthesis, In-Silico molecular modelling and biological studies of 1,4-Dihydroxyanthraquinone and its derivatives - Kisula, Lydia Mboje (Rhodes University, Faculty of Science, Department of Chemistry)
This current study of investigation reports on the synthesis of 1,4-dihydroxyanthraquinone and its derivatives on explorations of their medicinal potential. The study initially aimed to synthesize an analogue of a natural anthraquinone, 1,3,6-trihydroxy-7-((S)-1- hydroxyethyl)anthracene-9,10-dione 5 using Friedel-Crafts acylation of phthalic anhydride and a benzene derivative. Synthetic transformation of anacardic acid 63, obtained as a by- product of the cashew industry successfully afforded 4-ethoxyisobenzofuran-1,3-dione 89. However, when attempted to couple 4-ethoxyisobenzofuran-1,3-dione 89 with 2- hydroxyacetophenone 91 in a Friedel-Crafts acylation manner to form 2-acetyl-1,8- dihydroxyanthracene-9,10-dione 87 the reaction did not work efficiently. A simple derivative of benzene which is; benzene-1,4-diol 102 was reacted instead with 3-ethoxyphthalic acid 71 and isobenzofuran-1,3-dione 96 to form 1,4,5-trihydroxy anthraquinone 72 and 1,4- dihydroxyanthraquinone 42, respectively. A modified Marschalk reaction was then used to introduce the hydroxyl alkyl group to 1,4-dihydroxy anthraquinone 42, which allowed further elaboration of the hydroxyl-substituent in moderate to good yields (22-80%). A molecular docking study was performed using Schrödinger software to predict the binding affinity of the test compounds to the target protein trypanothione reductase (PDB ID: 6BU7). An in-vitro screening of 1,4-dihydroxyanthraquinone derivatives and some selected precursors for antitrypanosomal, antiplasmodial, antibacterial, and cytotoxicity activities produced encouraging results. Derivatives of anacardic acid and cardanol from CNSL were found to have moderate activity against trypanosomes with no activity against Plasmodium falciparum. Almost 63% of synthesized 1,4-dihydroxyanthraquinone derivatives displayed activity against trypanosomes. The in-vitro evaluation and the in silico molecular docking studies revealed that 1,4-dihydroxyanthraquinone derivatives can be potential drug-like candidates active against T.brucei parasites (IC50 = 0.70-1.20 Î¼M). Only four 1,4- iv dihydroxyanthraquinone derivatives with thiosemicarbazone, chloride, pyrrole, and diethanolamine functionality displayed activity against Plasmodium falciparum (IC50 = 3.17- 14.36 Î¼M). In-vitro evaluated of test compounds against antibacterial screen and cytotoxicity effects significantly showed that 2-hydroxy-6-pentadecylbenzoic acid 63a and 2-((2- chlorophenyl)(piperazin-1-yl) methyl)-1,4-dihydroxyanthracene-9,10-dione 78 have potency against Staphylococcus aureus and reduced the viability of the cells below 20% at an initial concentration of 50 Î¼g/mL. Only 1,4-dihydroxyanthraquinone derivatives with thiosemicarbazone 76, piperazine 78, and diethanolamine 80 motifs were active against HeLa cells and reduced the viability of cells below 20% at a concentration of 50 Î¼g/mL. In conclusion, this current reported study has generated useful knowlege on the applicability of the agro-waste CNSL as an agent active against trypanosomiasis but also as a low-cost starting material to synthesize hydroxy anthraquinones. The study has further given an overview to the understanding of the medicinal value 1,4-dihydroxyanthraquinone derivatives as promising candidates towards developing drugs suitable for treating neglected tropical diseases particularly trypanosomiasis.
Keywords: Computer simulation; Molecules Models; Dihydroxyanthraquinone; Trypanosomiasis; Leishmaniasis; Docking